Role of Incubation Center in Growth of Small-Scaled Businesses in Afghanistan (Global Journal of Management and Business Research, 2017)
For past three- years unemployment has been a growing in Afghanistan, which has caused many socio-economic problems. One of the solution to this problem is private sector development. A lot of attention has been paid toward attraction of investments at large scale from private sector, however, experience of many countries including industrial economies show that small scaled businesses has contributed to employment and economic development to remarkable extend. Small scaled businesses have a very high rate of failure at their initial stage. Development of these businesses requires promotion of entrepreneurship. This study attempts to highlight the role of business incubation centers for this purpose in Afghanistan context. Studies have shown that factors such as incubation centers physical infrastructure, provision of business assistance, management guidance and counselling, enabling environment and sound practices of incubation centers have led to survival and growth of many small businesses.
Keywords: incubation center; tenant companies; incubation